Gender and Pay Equity in a Global Knowledge Organisation - McGrath-Champ, Susan; Jefferson, Therese (CAER and IRRC, 2013)
The gender pay gap, the difference in earnings of men and women, has remainedremarkably resilient over the past two decades in Australia and a number of othercountries, despite a range of legislative and policy initiatives aimed at narrowing thisdifference. Drawing upon industry-wide data and an organisational case, this analysisof professional business services examines the nature of pay equity within and beyondorganisational boundaries. We conclude that ‘success’ in gender and pay equity termshas been constrained by minimum government compliance requirements and limitedattention to the role labour markets play in contributing to gendered patterns of pay.